Communication with patient in terms of elementary psychotherapy versus Gestalt psychotherapy. Experience from a workshop devoted to developing a relationship with the patient and using selected methods of therapeutic work - Ogórek-Tęcza, Beata (Nursing Problems / Problemy Pielęgniarstwa, 2023)
Developing a relationship with the patient and improving communication is very often connected with the resources of the person who initiates this relationship, and their awareness of their own mental processes is of considerable importance for shaping a relationship that will be supportive for the patient, but also safe within a relationship for the person coming into contact with the patient. Communication based on the fundamentals of Gestalt psychotherapy creates specific conditions for teaching a person to recognise observations and feelings or current emotions caused by experiencing an old situation that is unfavourably resolved or unfinished. This type of contact does not require much time, but it involves attention. Improving communication skills (in work-shops) allows people caring for the patient to be equipped with tools and techniques that, on the one hand, respond to the patient’s needs, and on the other hand, increase awareness of one’s own resources in a relationship.